CONCENTRATION OF STRESS AROUND THE CYLINDRICAL HOLE IN AN INITIAL STRESSED RECTANGULAR ORTHOTROPIC THICK PLATE - Yahnioglu, Nazmiye; Yesil, Ulku Babuscu (AMER SOC MECHANICAL ENGINEERS, 2010)
An orthotropic pre-stressed thick plate with a cylindrical hole under additional static loading on the upper face-plane of the plate have been studied within the framework of the Three-Dimensional Linearized Theory of Elasticity (TDLTE) in Initially Stressed Bodies. The corresponding problem formulation is presented and, in order to find the solution to this problem, the 3D finite element method is employed. The numerical results on the concentration of the stress around the cylindrical hole and the influence of the initial forces, geometrical and mechanical parameters on these concentrations are presented in graphical form and discussed. According to these results, in particular it is established that the stress distributions around the cylindrical hole changed significantly with the initial stretching or compressing forces.
Keywords: initial stress; stress concentration; cylindrical hole; orthotropic thick plate; 3D FEM; LAMINATED COMPOSITE PLATES; CIRCULAR HOLE; STRIP; Engineering